Analisis Kelengkapan Rekam Medis Berdasarkan SNARS di RSU Purwogondo Kebumen - Afrizal Noor Abidin; Novita Nuraini; Atma Deharja; Selvia Juwita Swari (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2022)
One of the hospital's quality is determined by a complete medical record document. The completeness of medical records at the Purwogondo General Hospital in Kebumen only reached 86% of the 100% standard determined by the minimum service. Completeness of medical records is needed in order to create continuity of treatment for patients and strong legal force. This study aims to analyze the completeness of medical records based on SNARS elements. The research subjects were 6 people, namely doctors, nurses, quality team representatives, medical recorders, internal supervisors, MIRM working group officers. Data collection methods are observation, interviews and brainstorming. The results of the research on the element of man are officer discipline and communication. The money element is the absence of a budget for the monitoring and evaluation team. The method element is the absence of an SOP for reviewing the completeness of medical records. The material element is the form design that the PPA has not yet understood. The machine element is the absence of an incomplete medical record control book, no monitoring and evaluation team for the completeness of medical records. Efforts to optimize the completeness of medical records are monitoring medical records on a regular basis and optimizing the monitoring and evaluation team.